Pengaruh Lingkungan Kerja dan Pelatihan Terhadap Produktivitas Karyawan PT. Sumber Bara Abadi (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of the work environment and training on employee productivity at PT. Sumber Bara Abadi, a coal mining company in East Kalimantan. The background of this study is based on the importance of creating a conducive work environment and effective training programs to improve employee efficiency and performance in the face of competitive industry competition. This study employs a quantitative approach by distributing questionnaires to the entire population of 70 permanent employees. The analysis method used is multiple linear regression to determine the partial and simultaneous effects of each variable. The results indicate that both the work environment and training have a positive and significant impact on employee productivity, both partially and simultaneously. The work environment was found to have a more dominant influence than training. The implications of these findings emphasize the importance for companies to create a comfortable and supportive work environment and to conduct relevant and continuous training in order to optimally enhance employee motivation and performance.